The design of a management information and control system for plant maintenance activities in an oil refinery - Chia, Ah Lay; Pakorn Adulbhan; Nakamura K.; Drew, Donald R.; Sharif, M. N.; Lee Foundation (Bangkok : Asian Institute of Technology, 1972)
The Bangchak Oil Refinery in Bangkok was selected for the purpose of the study. First, the background, the process and major equipment used of the Refinery were described. The elements of the management information and control system for plant maintenance activities in the Refinery were then identified and, explained. The manual control system of the Refinery was then described in detail. The code numbering system, maintenance records, and reports of the manual system which the Refinery was using, were presented; and some suggestions for improvement were made. Furthermore a computer-based control system was proposed and the dynamic system model for the proposed system was presented a Finally, a mathematical model for scheduling preventive inspection of the preventive maintenance system was presented with an hypothetical example illustrating how the model could be applied.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the-Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1972
Keywords: Petroleum refineries; Management information systems